Data analysis wind monitoring in the Republic of Tatarstan - E. V. Nasyrova; N. F. Timerbayev; O. V. Leukhina; I. Yu. Mazarov (Известия высших учебных заведений: Проблемы энергетики)
The paper presents the results of wind monitoring carried out in order to confirm the feasibility of building a wind farm in the Republic of Tatarstan. The task of wind monitoring is to determine and study the dynamics of the average annual wind regime and calculate the wind energy potential at promising sites for placing a wind power plant. On the given sites, after the annual cycle of meteorological parameters measurements, the average annual wind speeds, wind power, preferred directions, wind density, vertical profile of the wind flow and other data necessary for a detailed calculation of the wind power potential of the sites and the selection of specific models of wind generators and their arrangements for operation will be determined at these sites. An important component of the work performed is the development of methods for calculating wind potential at heights other than the heights of direct measurements.